Chemical Composition, In vitro and In silico Evaluation of Essential Oil from Ocimum tenuiflorum and Coriandrum sativum Linn for Lung Cancer - Singh, Bhim; Prajapati, Kumari S.; Kumar, Amit; Patel, Shivam; Kumar, Shashank; Jaitak, Vikas (Current Computer - Aided Drug Design, 2024)
Background: Medicinal plants play an essential role in everyday life; plants highly contain therapeutic phytoconstituents commonly used to treat various diseases. This paper discusses the Chemical composition, In vitro antiproliferative activity and In silico study of essential oil extracted from Ocimum tenuiflorum (family Lamiaceae) and Coriandrum sativum (family Apiaceae). Objective: In present study GC-MS was used to identify the chemical constituents from O. tenuiflorum and C. sativum. In vitro antiproliferative activity was performed on A549 cancer cell lines. In silico study was performed by Schrodinger’s maestro software to identify chemical constituents in both plants as potential EGFR inhibitors for the treatment of lung cancer. Methods: The essential oil was extracted by hydro distillation from aerial parts of O. tenuiflorum and C. sativum. The volatile oil sample was analyzed by (GC-MS) Gas Chromatography- Mass Spectrometry. Different chemical constituents were identified based on the retention index and compared with the NIST library. The oil samples from O. tenuiflorum and C. sativum was also evaluated for antiproliferative activity against human lung cancer A549 cell lines. In silico study was performed by Schrodinger maestro software against EGFR (PDB ID 5HG8). Results: O. tenuiflorum essential oil contains Eugenol (42.90%), 2-β-Elemene (25.98%), β- Caryophyllene (19.12%) are the major constituents. On the other side, C. sativum contains nnonadecanol- 1 (16.37%), decanal (12.37%), dodecanal (12.27%), 2-Dodecanal (9.67%), Phytol (8.81%) as the major constituents. Both the oils have shown in vitro antiproliferative activity against human lung cancer cell lines A549 having IC50 values of 38.281 μg/ml (O. tenuiflorum) and 74.536 μg/ml (C. sativum). Molecular interactions of constituents hydro distilled from two oils was analysed by schrodinger maestro software against EGFR (PDB ID 5HG8). Conclusion: The oil sample extracted from O. tenuiflorum showed more antiproliferative activity than C. sativum. In silico study showed that two chemical constituents, namely di-isobutyl phthalate (-7.542 kcal/mol) and dibutyl phthalate (-7.181 kcal/mol) from O. tenuiflorum and one diethyl phthalate (-7.224 kcal/mol) from C. sativum having more docking score than standard Osimertinib which indicates the effectiveness of oils for lung cancer.
Keywords: EGFR